Field evaluations of 14 sweet cherry cultivars as pollinators for cv. Regina (Prunus avium, L.) - Thurzó, S.; Grandi, M.; Lagezza, L.; Lugli, S.; Holb, I. J.; Szentpéteri, T.; Nagy, P. T.; Szabó, Z.; Soltész, M.; Nyéki, J.; Sansavini, S. (International Journal of Horticultural Science, 2007)
In this study, the pollen of 14 sweet cherry cultivars (‘Anella’, ‘Duroni 3’, ’Badacsony’, ’Cristalina’, ’Ferbolus’, ’Ferrovia’, ’Georgia’, ’Hudson’, ’Kordia’, ’Sam’, ’Schneiders’, ‘Spate’, ‘Knorpelkirsche’, ’Skeena’, ’Summit’, ’Sylvia’) was used to fertilize the emasculated flowers of sweet cherry cv. ’Regina’. Fruit set was assessed three times during fruit development: 14 May, 30 May and 27 May 2007. We observed full incompatibility among the 14 cultivars for cv. ’Cristalina’, which is in the same S-allele group as cv. ’Regina’. After analysis of our data, we have results about fertilization efficiency of the cultivars. Most of the evaluated cultivars are inadequate to fertilize cv. ’Regina’ to a sufficient degree. There were two exceptions, cv. ’Sam’ and cv. ’Skeena’, where percentage of ripened fruits was above 20%. These two cultivars can guarantee such a pollination, which ensures ample quantity of ripened fruits. Results of this study have proved three other cultivars to be quite good pollinators for cv. ’Regina’. In conclusion, ideal pollinators for cv. ’Regina’ could be — apart from above-mentioned two cultivars, ’Sam’ and ’Skeena’ — cvs. ’Sylvia’ and ’Bianca’, which was suggested by more literature sources.